Thermodynamics of harmony: Extending the analogy across musical systems - L. Nasser; A. Tillotson; X. Hernandez (PLoS ONE, 2025)
It is common for most people to think of science and art as disparate, or at most only vaguely related fields. In physics, one of the biggest successes of thermodynamics is its explanation of order arising from disordered phases of matter through the minimization of free energy; In 2019, Berezovsky showed [1] that the mechanism describing emergent order from disorder in matter can be used to explain how ordered sets of pitches can arise out of disordered sound, thus bridging the gap between science and the arts in a powerful way. In this paper we analyze his method in detail, generalizing it beyond the 12 tone system of intonation of Western music by explicitly considering Gamelan instruments and clarifying some details in the hope of strengthening it and making it better known and recognized.